THE USE OF GOOGLE CLASSROOM FOR DISTANCE LEARNING IN THE CURRENT COVID-19 SITUATION AT THE VOCATIONAL SCHOOL CONTEXTS IN INDONESIA - Lia Novita; Pupung Purnawarman; Didi Suherli (English Review: Journal of English Education, 2022)
The aims of this study are to find out how to implement optimization using Google classroom in the distance learning process at vocational school, students’ response towards it, and whether it can achieve the learning objectives at vocational school. This qualitative study used exploratory sequential mixed methods with observation and questionnaires, analyze the results and then strengthen it with quantitative research (test) by using two groups consisting of the experimental group and the control group. This research was carried out in one of the existing Vocational Schools in West Java and used the 184 twelfth grade students of the academic year 2020/2021 using purposive sampling technique. The sample was the students from Computer and Network Engineering program, each subject taken from the population is chosen intentionally based on the class group selection. For data collection techniques, this study used observation, questionnaire with closed ended question, and test. Based on the data, the results of this research that have been carried out, that: (1) application of optimization using Google classroom in the Distance Learning process shows that the Distance Learning process carried out which run well and in accordance with classroom learning procedures starting from making classes, changing the old class themes, making general information about subjects, making subject matter, making and starting assignments, students working on assignments, until the teacher evaluates the results of the assignment. (2) Student responses to the use of Google classroom for Distance Learning were very good. (3) Distance Learning using Google classroom can achieve the learning objectives.